The Contents of Colombia’s Recent History and its Selection Criteria by Social Science Teachers in Two Educational Institutions in the City of Medellín: What is the Recent History Taught? - Tabares Ospina, Anderson (2022)
This article derives from a master’s thesis carried out within the framework of the XIX cohort of the master’ degree in Education of the Faculty of Education of the University of Antioquia, in which the subject positions of Social Sciences teachers in the teaching of the Recent History of Colombia in two educational institutions in the city of Medellín were investigated. Among other aspects, they were asked about the contents of recent history teaching and their selection criteria, and it was found that the Colombian armed conflict since the 1950s has been a central element in the teaching process and that its arrival in the classroom is due more to personal initiatives of teachers or demands of students than to normative guidelines.